Innovative Public Policies to Encourage Investment, Trade, Growth and Development in Peru - Durand Carrión, Julio Baltazar (2015)
Are public institutions, the main challenge for Peruvian regulators implement measures and policies to achieve the goal of expanding coverage of regulating utilities, ensuring minimum quality levels to fair rates. Regulators have also to play a role in protecting the rights of consumers, which have instruments that limit or restrict positions abuse by companies that provide services.